Pengaruh kualitas layanan, harg dan kepuasan pelanggan terhadap loyalitas penonton untuk menonton film - UNTUNG SANJAYA; KLEMENS WEDANAJI PRASASTYO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2016)
The purpose of this research is to test and investigate the influence of service quality, price, costumer satisfication to costumer loyality at Blitzmegaplex. The object of this study are consumers of Blitzmegaplex that watch movie in Blitzmegaplex in Central Park, West Java. Data for this study comes from primary source by distributing Five-Point Likert-Scale questionnaires to gather 250 sample. The data is then analyzed with AMOS and the result show that service quality, price, costumer satisfication have influence to costumer loyality.